Aptamer‐Based Screen of Neuropsychiatric Lupus Cerebrospinal Fluid Reveals Potential Biomarkers That Overlap With the Choroid Plexus Transcriptome. Issue 7 (18th May 2022) - Vanarsa, Kamala; Sasidharan, Prashanth; Duran, Valeria; Gokaraju, Sirisha; Nidhi, Malavika; Titus, Anto Sam Crosslee Louis Sam; Soomro, Sanam; Stock, Ariel D.; Der, Evan; Putterman, Chaim; Greenberg, Benjamin; Mok, Chi Chiu; et al.
Abstract : Objective: As no gold‐standard diagnostic test exists for neuropsychiatric systemic lupus erythematosus (NPSLE), we undertook this study to execute a broad screen of NPSLE cerebrospinal fluid (CSF) using an aptamer‐based platform. Methods: CSF was obtained from NPSLE patients and subjected to proteomic assay using the aptamer‐based screen. Potential biomarkers were identified and validated in independent NPSLE cohorts in comparison to other neurologic diseases. Results: Forty proteins out of the 1, 129 screened were found to be elevated in NPSLE CSF. Based on enzyme‐linked immunosorbent assay validation, CSF levels of angiostatin, α2‐macroglobulin, DAN, fibronectin, hepatocellular carcinoma clone 1, IgM, lipocalin 2, macrophage colony‐stimulating factor (M‐CSF), and serine protease inhibitor G1 were significantly elevated in a predominantly White NPSLE cohort (n = 24), compared to patients with other neurologic diseases (n = 54), with CSF IgM (area under the curve [AUC] 0.95) and M‐CSF (AUC 0.91) being the most discriminatory proteins. In a second Hong Kong–based NPSLE cohort, CSF IgM (AUC 0.78) and lipocalin 2 (AUC 0.85) were the most discriminatory proteins. Several CSF proteins exhibited high diagnostic specificity for NPSLE in both cohorts. Elevated CSF complement C3 was associated with an acute confusional state. Eleven molecules elevated in NPSLE CSF exhibited concordant elevation in the choroid plexus, suggesting shared origins. Conclusion: Lipocalin 2, M‐CSF, IgM, and complement C3 emerge as promising CSF biomarkers of NPSLE with diagnostic potential.